2008
DOI: 10.1099/jmm.0.47152-0
|View full text |Cite
|
Sign up to set email alerts
|

Cefoxitin disc diffusion test for detection of meticillin-resistant staphylococci

Abstract: Staphylococci are the main causative agents of nosocomial diseases. Over the last few years, the increase in the number of meticillin-resistant (MR) staphylococci has become a major clinical problem. Accuracy and promptness in the detection of meticillin resistance are of key importance in ensuring the correct antibiotic treatment in infected patients and control of MR staphylococci in the hospital environment. This study evaluated the accuracy of a cefoxitin disc diffusion (DD) test for the detection of metic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 20 publications
1
34
1
1
Order By: Relevance
“…The MRSA strains were identified using oxacillin disc (1μg), cefoxitin disc (30µg) as reported by various authors 16 and slidex staph latex agglutination tests (bioMerieux) which detects methicilin resistance in Staphylococci based on the production of low-affinity PBP2a, which is encoded by the mecA gene .…”
Section: Methodsmentioning
confidence: 99%
“…The MRSA strains were identified using oxacillin disc (1μg), cefoxitin disc (30µg) as reported by various authors 16 and slidex staph latex agglutination tests (bioMerieux) which detects methicilin resistance in Staphylococci based on the production of low-affinity PBP2a, which is encoded by the mecA gene .…”
Section: Methodsmentioning
confidence: 99%
“…Accuracy and promptness in the detection of methicillin resistance is very much important in ensuring correct antibiotic treatment in the infected patients so that the control of MRCONS can be achieved in the hospital environments. [5] Slime is one of the virulence marker which is believed to make the microorganism insusceptible to certain antibiotics. [6] Detection of slime producing and beta-lactamase producing strains help in establishment of CONS as a pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Even Swenson et al, Jain et al, (22,23) showed 100% specificity and sensitivity with cefoxitin disc methods. Our findings also emphasis that cefoxitin disc method is close enough to PCR in identifying MRSA.…”
Section: Discussionmentioning
confidence: 98%